Cinética de remoção de matéria orgânica e coliformes termotolerantes em lagoas facultativas - Alcantara, Paulo Coelho de (2019)
The present study arises from the need to better discuss and integrate design parameters in orderto represent the real behavior of treatment systems through stabilization ponds with greaterprecision. Stabilization ponds are widely used worldwide for wastewater treatment of domesticand industrial effluents. The system is traditionally composed of serial (anaerobic, facultativeand maturation) lagoons, with each pond playing a different role in the removal of pollutantsand after treatment, the effluent must meet the standards required to return to the water body ormainly reused. as irrigation water. This paper aims to investigate the influence of applied massloads and the kinetic removal coefficients for organic matter and thermotolerant coliforms usingthe perfectly mixed, pistonate and dispersed flow reactor models. It was verified the influence ofthe dispersion number in the lagoons, for the pollutants removal, the applied and the removedload employed in a set of ten full scale stabilization ponds in the operational conditions and theexpected performance. Different models were computed to estimate dispersion coefficients andfirst order removal constants. The results showed no considerable distinctions between waysof estimating d, and it is possible to employ structured models from the geometry of lagoons,because they are simpler. Higher accuracy was achieved with estimates of k (kbekDBO) obtainedfrom empirical formulations based on the applied load criterion. Such an approach will offermore reliable effluent quality prediction estimates. The present study arises from the need tobetter discuss and integrate design parameters in order to represent the real behavior of treatmentsystems through stabilization ponds with greater precision.